A roadmap to building first responder networks: Lessons learned and best practices from Belgium and Switzerland - Esther Moens; Eva Degraeuwe; Maria Luce Caputo; Ruggero Cresta; Robin Arys; Nina Van Moorter; Thomas Tackaert; Claudio Benvenuti; Angelo Auricchio; Steven Vercammen (Resuscitation Plus, 2023)
Background/Aims: Limited bystander assistance and delayed emergency medical service arrival reduce the chances of survival in cardiac arrest victims. Early basic life support through trained first responders (FR) and automatic external defibrillation both improve the outcome. Well-organized FR networks have shown promise, but guidance on effective implementation is lacking. This study evaluates two FR networks, in Belgium and in Switzerland, to identify main advancements in the development of such systems. Method: Direct comparison is made of the barriers and facilitators in the development of both FR systems from 2006 up until December 2022, and summarized within a roadmap. Results: The Roadmap comprises four integral steps: exploration, installation, initiation, and implementation. Exploration involves understanding the national legislation, engaging with advisory bodies, and establishing local steering committees. The installation phase focuses on FR recruitment, engaging specific professional groups such as firemen, registering public Automated External Defibrillators (AEDs), and requesting feedback. The initiation step includes implementing improvement cycles and fidelity measures. Finally, implementation expands the network, leading to increased survival rates and the integration of these practices into legislation. A significant focus is placed on FR's psychological wellbeing. Moreover, the roadmap highlights the use of efficient geo-mapping to simplify optimal AED placement and automatically assign FRs to tasks. Conclusion: The importance of FR networks for early resuscitation is increasingly recognized and various systems are being developed. Key developmental strategies of the EVapp and Ticino Cuore app system may serve as a roadmap for other systems and implementations within Europe and beyond.